Biological nitrification inhibition (BNI): is it a widespread phenomenon? - Subbaraoa, Guntur V.; Rondón, Marco Antonio; Ito, O.; Ishikawa, T.; Rao, Idupulapati M.; Nakahara, K.; Lascano Aguilar, Carlos Eduardo; Berry, W.L. (Springer, 2007)
Regulating nitrification could be a key strategy in improving nitrogen (N) recovery and agronomic N-use efficiency in situations where the loss of N following nitrification is significant. A highly sensitive bioassay using recombinant luminescent Nitrosomonas europaea, has been developed that can detect and quantify the amount of nitrification inhibitors produced by plants (hereafter referred to as BNI activity). A number of species including tropical and temperate pastures, cereals and legumes were tested for BNI in their root exudate. There was a wide range in BNI capacity among the 18 species tested; specific BNI (AT units activity g?1 root dry wt) ranged from 0 (i.e. no detectable activity) to 18.3 AT units. Among the tested cereal and legume crops, sorghum [Sorghum bicolor (L.)], pearl millet [Pennisetum glaucum (L.) R. Br.], and groundnut [Arachis hypogaea (L.)] showed detectable BNI in root exudate. Among pasture grasses, Brachiaria humidicola (Rendle) Schweick, B. decumbens Stapf showed the highest BNI capacity. Several high- and low-BNI genotypes were identified within the B. humidicola species. Soil collected from field plots of 10 year-old high-BNI genotypes of B. humidicola, showed a near total suppression (>90%) of nitrification; most of the soil inorganic N remained in the NH 4 + form after 30 days of incubation. In contrast, soils collected from low-BNI genotypes did not show any inhibitory effect; most of the soil inorganic N was converted to NO 3 – after 30 days of incubation. In both the high- and low-BNI genotypes, BNI was detected in root exudate only when plants were grown with NH 4 +, but not when grown with NO 3 – as the sole source of N. BNI compounds when added to the soil inhibited nitrification and the relationship was linear (r 2 = 0.92**; n = 12). The BNI from high- and low-BNI types when added to N. europaea in pure culture, blocked both the ammonia monooxygenase (AMO) and the hydroxylamine oxidoreductase (HAO) pathways. Our results indicated that BNI capacity varies widely among and within species; and that some degree of BNI capacity is likely a widespread phenomenon in tropical pasture grasses. We suggest that the BNI capacity could either be managed and/or introduced into pastures/crops with an expression of this phenomenon, via genetic improvement approaches that combine high productivity along with some capacity to regulate soil nitrification process.